Understanding the Effects of Selected Backpack Loads Carried for Certain Durations on Peak Forces of Walking Gait in School-Going Boys - Rabiya Husain; Dessalegn Wase Mola; Dhananjoy Shaw (Journal of Learning Theory and Methodology)
Background. Backpacks are commonly used by students to carry their school items. However, increasing backpack loads can lead to negative effects on health and posture, particularly through changes in gait dynamics. Peak forces are a critical variable in understanding gait mechanics, which is significantly impacted by carrying loads. Therefore, it is crucial to investigate the changes in peak forces with varying (increasing) backpack loads and the durations of carrying.